Ombra : Supernatural Music in the Eighteenth Century. - McClelland, Clive (Lexington Books, 2012)
Ombra is the musical language employed when a composer wishes to inspire awe and terror in an audience. Clive McClelland's Ombra: Supernatural Music in the Eighteenth Century explores the large repertoire of such music, focusing on the eighteenth century and Mozart in particular. He discusses a wide range of examples drawn from theatrical and sacred music, eventually drawing parallels between these features and Edmund Burke's 'sublime of terror, ' thus placing ombra music in an imp.